Information on radiotherapy schedulle interruptions using Mosaiq (Revista de Física Médica, 2022)
A methodology is presented to get automatically from the  database of an oncologic information system, those data that  are needed to monitor interruptions in radiotherapy  treatments, on a quick and reliable way.
Keywords: Interruption management; oncologic information system; radiotherapy schedule